CLUSTER OF THE GOLDEN RATIO IN THE FIBONACCI SEQUENCE-AN ANALYTICAL STUDY ON THE DOW JONES INDEX - Haider Nasser Hussein Al Mayali; Hawraa Zaki Hameed; Hussein Ahmed Alsafi (Scholars Digest Publishing, 2023)
The aim of this research is to analyze the golden ratio cluster in the Fibonacci platform, as this platform is considered one of the most important platforms used in technical analysis, and the ground of it is price discovery or price prediction to attract or sell. In addition, the gold ratio and Fibonacci numbers have attracted the benefit of mathematicians. Artists, architects, sculptors and musicians for centuries, the golden ratio was associated with ancient Greek arts and architecture, and the Fibonacci series was discovered, which is linked to the golden ratio. The current study used the Dow Jones Index as a sample for analysis. It is worth noting that the Dow Jones Index is considered one of the most important global indicators used in technical analysis and price discovery. The current study has reached a set of conclusions, the most important of which is that the Fibonacci platform helps and contributes greatly in providing results that help investors in Make buying and selling decisions due to the accurate and quick recommendations it provides.